The effect of applying a vestibular rehabilitation program on the level of activity-related balance and cognition of patients with post-stroke dizziness (Journal of Hama University, 2025)
Globally, stroke is the second leading cause of death and the third most common cause of disability. About 15 million people annually suffer from a stroke for the first time, and a third of these cases result in death. Stroke patients suffer from various disorders, including balance disturbance, dizziness, and irregular standing, which exposes them to the risk of falling. Hence the importance of implementing a vestibular rehabilitation program. Therefore, the current quasi-experimental study aimed to evaluate the effect of applying a vestibular rehabilitation program on the level of activity-related balance and cognition of patients with post-stroke dizziness. This research was conducted on an available sample of 40 male and female patients who will be selected using the available sample method and will be divided into two groups (a control group left for regular physical therapy in the hospital and an experimental group to which a vestibular rehabilitation program is applied). Data for the current study was collected after reviewing the literature related to the research topic using the tool. It consists of two parts: the first part includes demographic and clinical data, and the second part: the balance measure for activities: DIZZINESS HANDICAP INVENTORY (DHI). The study showed that stroke patients who suffer from dizziness showed a lower level of disability after applying the vestibular rehabilitation program than patients with dizziness. Stroke patients who suffer from dizziness and undergo regular physical rehabilitation. The study recommended generalizing the results of the current research experiment and re-applying it in other hospitals, and conducting this study on a larger sample that includes a larger number of stroke patients.
Keywords: Stroke